(3LGeY eSGFd GdCMcGe deG fRd HGdbVGjG ef GdeaJjf hGdCMcGes - (3eMeO Hf CMeO Hf eMeO GdHQRGdj GdeZQHj GdeGdcj, CHh GdbGSe,J (B844 (3g` s
(3ChdgG (B:s
(3bdJ XGgQ gPG Cf GdLGQjI dGJWdH HGdNQhL eY ef jSJMb s
(3BNQgG (B:s
"(3QHfG dGJDGNPfG Ef fSjfG Ch CNWCfG QHfG hdGJMed YdjfG CUQkG ceG MedJg Ydi GdPjf ef bHdfG QHfG hdGJMedfG eG dGWGbI dfG Hg hGYahG YfG hGZaQ dfG hGQMefG CfJ ehdGfG aGfUQfi Ydi Gdbhe GdcGaQjf(B" (3fLR GdLRA GdQGHY ef GdfhGRd hHg JeGe GdcJGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B358s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs